2010
DOI: 10.1590/s1415-47572010005000074
|View full text |Cite
|
Sign up to set email alerts
|

The insulin polymorphism -23Hph increases the risk for type 1 diabetes mellitus in the Romanian population

Abstract: The insulin -23Hph and IGF2 Apa polymorphisms were genotyped in Romanian patients with T1DM (n = 204), T2DM (n = 215) or obesity (n = 200) and normoponderal healthy subjects (n = 750). The genotypes of both polymorphisms were distributed in concordance with Hardy-Weinberg equilibrium in all groups. The -23Hph AA genotype increased the risk for T1DM (OR: 3.22, 95%CI: 2.09-4.98, p < 0,0001), especially in patients without macroalbuminuria (OR: 4.32, 95%CI: 2.54-7.45, p < 0,0001). No other significant association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Mathematical models estimate that, adding the HLA and VNTR contribution, up to 60% of the total genetic component of T1D is obtained [ 19 ]. VNTR polymorphisms located in the insulin promoter, 596 bp upstream of the insulin start codon, consist of a highly polymorphic tandem repeat sequence ACAGGGGTGTGGGG (14 pb) whose variants are grouped into three classes of alleles according to their length [ 20 , 21 ]. Regarding our population, VNTR is in linkage disequilibrium with rs689 where class I VNTR allele is associated with autoimmunity and inherited linked to the Adenine SNP allele.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models estimate that, adding the HLA and VNTR contribution, up to 60% of the total genetic component of T1D is obtained [ 19 ]. VNTR polymorphisms located in the insulin promoter, 596 bp upstream of the insulin start codon, consist of a highly polymorphic tandem repeat sequence ACAGGGGTGTGGGG (14 pb) whose variants are grouped into three classes of alleles according to their length [ 20 , 21 ]. Regarding our population, VNTR is in linkage disequilibrium with rs689 where class I VNTR allele is associated with autoimmunity and inherited linked to the Adenine SNP allele.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the presence of autoantibodies and a high-risk HLA genotype, individuals carrying class III VNTR alleles present a significant reduction in the probability of developing the disease [ 24 , 25 ]. Based on this association, major studies have used 23HphI (rs689) as an associated marker to study the VNTR [ 21 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they showed that the A/A genotype rather than the T/T genotype was associated with higher mean BMI and waist circumference (Huede et al 2004;Le Stunff et al 2001). In contrast, no significant associations between the INS polymorphisms with childhood and adult obesity among the Europeans (Bouatio-Naji et al 2008;Cimponeriu et al 2010), and with body composition in early childhood (Maas et al 2010) were reported. In our study, there was also lack of association between the INSR rs3745551 and childhood obesity in the Malay population.…”
Section: Discussionmentioning
confidence: 99%